THE HUMAN HAIR FOLLICLE AS BATTERY WITH SHAFT AS BIPOLAR EXTENSION INTRODUCING IN VITRO EXPERIMENTS DEMONSTRATING PRESENCE OF BIPOLAR ELECTRICAL CHARGES INHERENT IN THE HUMAN HAIR SHAFT INDUCED BY THE FOLLICLE’S DC CURRENTS - Embi, Abraham A. (International Journal of Research -GRANTHAALAYAH, 2022)
The main purpose of this manuscript is to enumerate prior published in vitro individual findings by this author and others with the ultimate goal to demonstrate the human hair similarity with a DC battery. This by the hair root as the energy source and the hair shaft as a bipolar (+−) extension of the follicle’s DC currents. The human hair consists of a follicle anchored in the skin and a protruding shaft, it has also been described as a miniorgan, having its own cells division, metabolism and known to undergo aging stages; eventually reaching a point where the old hair sheds and a new hair growing cycle begins from the same follicular tissue. Using sophisticated magnetometers, magnetic fields emitted by direct currents (DC) in human hair follicle was detected and introduced in 1980. Most recently in 2015, a tabletop optical microscopy method was developed and published in 2016, thus allowing for the detection of hair follicles and shafts magnetic fields. Utilizing this novel microscopy technique, this author and others were able to again identify the follicle and shaft magnetic fields by interacting with cyano-compounds powder in solution. Qualitative images are presented where the bipolar property of the shaft is inferred by using fresh blood on a glass slide. This inference was rationalized since blood tissue material is known to express negative charges, thus repelled by an equal charge. The shaft is repeatedly shown in experiments to express a contralateral positive side. The positive side triggering fibrin formation documented by images showing intricate networks indicative of undergoing blood coagulation. Conversely, the contralateral negative side is shown as repelling blood tissue, thus inhibiting coagulation. Additionally, other experiments elucidate the follicle as a DC energy source; and the hair shaft as its bipolar extension.